Factors Affecting Speech Delay in Children Under 5 Years Old at YARSI Hospital and Its Review from an Islamic Perspective - Muhammad Farabi Izka; Elsye Souvriyanti; Tuty Herawaty; Fazlurrahman Anshar (Eduvest - Journal of Universal Studies, 2026)
Speech delay is one of the most common developmental issues in early childhood, affecting 5-10% of preschool children in Indonesia with an increasing trend annually. This study aims to identify internal and external factors influencing speech delay in children under 5 years old at YARSI Hospital. Using a quantitative observational analytic approach with a cross-sectional design, data were collected from 102 children diagnosed with speech delay through total sampling over a 6-month period. Results showed that speech delay was more prevalent in boys (69.6%) and children aged 49-59 months (31.4%). Internal factors identified include genetic and family history (29.4%), intelligence level, physical disability (15.7%), and prematurity (6.9%). External factors include parental education, parenting style with permissive pattern being dominant (44.1%), socioeconomic status with most families in low to medium categories (46.1% and 44.1%), gadget use, parental employment, and foreign language exposure (29.4%). This study concludes that speech delay is a multifactorial condition influenced by the interaction between internal biological factors and external environmental factors. From an Islamic perspective, children are an amanah from Allah SWT, and speech delay should be addressed through comprehensive efforts involving medical, educational, social, and spiritual approaches with patience and consistent stimulation.